Generalized anxiety disorder symptoms among persons with diagnosed HIV in the United States. (1st September 2019) - Beer, Linda; Tie, Yunfeng; Padilla, Mabel; Shouse, R. Luke
Abstract : Objective: To estimate the prevalence of generalized anxiety disorder (GAD) symptoms among adults with diagnosed HIV (PWH) in the United States in order to inform effective HIV prevention and care efforts. Design: The Medical Monitoring Project (MMP) is a complex sample survey of adults with diagnosed HIV in the United States. Methods: We used MMP data collected during June 2015 to May 2016 to calculate the weighted prevalence of GAD symptoms among PWH ( N = 3654) and prevalence ratios with predicted marginal means to evaluate significant differences between groups. Results: The estimated prevalence of GAD symptoms among PWH was 19%. GAD symptoms were associated with significantly lower antiretroviral therapy prescription and adherence, medical HIV care engagement, and sustained viral suppression. Persons with GAD symptoms were over three times as likely to have an unmet need for mental health services (23 vs. 7%) and had significantly more emergency room visits and hospitalizations than those without these symptoms. GAD symptoms were associated with significantly higher prevalence of condomless sex while not sustainably virally suppressed with a person not known to be taking preexposure prophylaxis (9 vs. 6%). Conclusion: GAD symptom prevalence among PWH was considerably higher than among the US general adult population, indicating an excess burden of anxiety among PWH. Outcomes along the HIV care continuum were poorer, and risk for HIV transmission was higher, among persons with symptoms. Incorporating routine screening for GAD in HIV clinical settings may help improve health outcomes, reduce HIV transmission, and save healthcare costs.